Pressure Ulcers: Risk Stratification and Prognostic Factors That Promote Recurrence After Reconstructive Surgery - Wimon Sirimaharaj (2018)
© The Author(s) 2018. The aim of this study was to identify overall recurrence rates after reconstructive surgery in patients with pressure ulcers and to identify risk factors that associated with recurrence after reconstructive surgery. This study was done in Faculty of Medicine Chiang Mai University, including recurrence at the same site as well as on new sites, between January 1998 and December 2015. 165 patients with 272 pressure ulcers were retrospectively collected and analyzed. The overall pressure ulcer recurrence rate was 16.54% (45 from 272 ulcers) from an overall patient recurrence of 19.39% (32 from 165 patients). From multivariable analysis, we found 9 prognostic factors that were statistically significant for recurrence after surgery, divided into 2 groups: uncontrollable and controllable factors. Uncontrollable factors consisted of being female (hazard ratio [HR]=1.90;95%CI=1.54-2.34), being older than 45 years (HR=1.67;95%CI=1.40-2.0), and location of pressure ulcers on ischium (HR=1.65; 95% CI=1.51-1.80) and sacrum (HR=1.17;95%CI=1.10-1.23). Controllable factors included spasticity (HR=1.11;95%CI=1.04-1.20), incomplete healing before discharge (HR=5.42;95% CI=3.95-7.44), serum albumin level ≤3 g/dL (HR=1.27;95%CI=1.13-1.43), pressure ulcer stage 4 (HR=1.90;95%CI=1.41-2.54), non -muscle-based procedure (HR=3.82;95%CI=2.54-5.76), and length of hospitalization >21 days (HR=2.94;95%CI=1.60-5.40). Patients with these factors were strongly advised to address and improve all these factors for decreasing the recurrence rate after reconstructive surgery.